Competitiveness of flooded rice cultivars with a red rice simulating cultivar - Junior, Alvadi Antonio Balbinot; Fleck, Nilson Gilberto; Menezes, Valmir Gaedke; Agostinetto, Dirceu (Pesquisa Agropecuaria Brasileira, 2003)
Morphologic and physiologic characteristics of crop plants can affect their competitive ability with weeds. This research aimed to investigate competitiveness of flooded rice (Oryza sativa L.) cultivars with a red rice simulating genotype. It was investigated, during the 2000/2001 warm season, the behavior of eight rice genotypes, grown in presence or absence of the rice cultivar EEA 406, simulating a red rice infestation. At 45 and 60 days after rice seeding, it was evaluated the response of red rice mimicker genotype in relation to rice cultivars. At harvest, it was determined plant height, yield components, and grain yield of the cultivars. The late season genotype IR 841 suppressed growth of the simulative cultivar, presenting, together with the very-early cultivar Ligeirinho, the lowest reductions in grain yield under competition. In opposite, IAS 12-9 Formosa and Bluebelle cultivars allowed the greatest growth and seed production by the concurrent rice, also presenting the largest decreases of grain yield under the competition condition.
Keywords: Oryza sativa; plant competition; weeds; crop management